Perbandingan tingkat kepatuhan pasien hipertensi yang diberikan konseling dengan alat bantu pesan pengingat dan brosur - Akhmad Junaidi; Herliana Dewi; Hendrya Legenda; Dita Ayulia Dwi Sandi; Satrio Wibowo Rahmatullah; Karunita Ika Astuti (BORNEO JOURNAL OF PHARMASCIENTECH, 2021)
Hypertension is a condition with blood pressure in 140/90 > mmHg. Medication compliance in hypertension patient can control blood pressure. Complience can improve with counseling and use tools of counselling. The aim of this study was to know the effect of counselling with the tools i.e an SMS reminder and brochure for compliance of hypertension patient. The study was observational analytical study by using the instrument of Adherence Morisky questionnaire Modified Scale (MMAS-8) to measure the level of compliance of the patient. Patients (n=61) were divided into 3 groups i.e the patients were only given counselling, given counselling and sms reminder (2 weeks), given counseling and brochures. Results of this study was compliance levels respectively high, medium and low were 21.74%; 43.48% and 34.78% (group counselling), 46.67%; 13.33% and 40% (group counseling and sms reminder) and 39.13%; 34.78% and 26.09% (group counseling and brochures). There was effect of counselling with an SMS reminder and brochure for compliance of hypertension patient (sig. 0,000) and there was no difference for compliance of hypertension patients in patients who given counseling with an SMS reminder or brochure (sig 0,497)